Blood eosinophil count and prospective annual asthma disease burden: a UK cohort study. Issue 11 (November 2015) - Price, David B; Rigazio, Anna; Campbell, Jonathan D; Bleecker, Eugene R; Corrigan, Christopher J; Thomas, Mike; Wenzel, Sally E; Wilson, Andrew M; Small, Mary Buatti; Gopalan, Gokul; Ashton, Valerie L; Burden, Anne; et al.
Summary: Background: Elevated sputum eosinophil counts predict asthma exacerbations and responsiveness to inhaled corticosteroids but are impractical to measure in primary care. We investigated the relation between blood eosinophil count and prospective annual asthma outcomes for a large UK cohort. Methods: This historical cohort study used anonymised medical record data to identify primary care patients with asthma aged 12–80 years with 2 years of continuous records, including 1 year before (baseline) and 1 year after (outcome) their most recent eosinophil count. Negative binomial regression was used to compare outcome exacerbation rates and logistic regression to compare odds of asthma control for patients with blood eosinophil counts of 400 cells per μL or less versus greater than 400 cells per μL, adjusting for age, sex, body-mass index, smoking status, and Charlson comorbidity index. The study is registered at ClinicalTrials.gov, number NCT02140541 . Findings: Overall, 20 929 (16%) of 130 248 patients had blood eosinophil counts greater than 400 cells per μL. During the outcome year, these patients experienced significantly more severe exacerbations (adjusted rate ratio [RR] 1·42, 95% CI 1·36–1·47) and acute respiratory events (RR 1·28, 1·24–1·33) than those with counts of 400 cells per μL or less. They also had significantly lower odds of achieving overall asthma control (OR 0·74, 95% CI 0·72–0·77), defined as limited reliever use and no asthma-related hospital attendance or admission, acute course of oral corticosteroids, or prescription for antibiotics. Exacerbation rates increased progressively with nine ascending categories of blood eosinophil count as compared with a reference category of 200 cells per μL or less. Interpretation: Patients with asthma and blood eosinophil counts greater than 400 cells per μL experience more severe exacerbations and have poorer asthma control. Furthermore, a count–response relation exists between blood eosinophil counts and asthma-related outcomes. Blood eosinophil counts could add predictive value to Global Initiative for Asthma control-based risk assessment. Funding: Teva Pharmaceuticals.